The Reproductive Behaviour of the Kittiwake (Rissa tridactyla) - Nikolaas Tinbergen (British Film Institute, 1956)
(en)The film gives a detailed study of the courtship, mating and parenthood of the kittiwake. Shot in the Faroe Isles.